THE USING OF READING METHOD IN THE PROCESS OF FOREIGN STUDENTS' LANGUAGE AND CULTURAL ADAPTATION IN THE USA HIGHER EDUCATIONAL INSTITUTIONS - Yaroslav Slutskiy ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The author analyzes the programs of the USA higher education institutions that use the method of reading in the formation of foreign students' linguistic and cultural patterns, increase the effectiveness of communication activities and understanding of socio-cultural characteristics of the host country. The characteristics of reading allowed to determine that this method has the features of the process (which is transformed into certain actions that aimed at achieving the delivered goal) and the product (the using of aspects of achieving the goal in a certain sequence, which is necessary for process efficiency). The author considers strategies (descending and ascending) that promote the reading comprehension and are necessary for the linguistic and cultural patterns formation, because only when understanding the textual information, the personality of a foreign student is able to form the necessary elements that will later be applied in practice.